Discussion on the issues of applying OTN in power grid communications - Xinnan CHEN; Weihua LIAN; Yining MA (Dianxin kexue)
With the gradual increase in the demand for communication bandwidth in the electric power grid, the application of optical transport network (OTN) in electric power communication has become increasingly extensive and in-depth.A series of problems to be solved have been found in the application process.The long-haul transmission problem, the interruption problem of OTN with polarization multiplexing carried by OPGW which is caused by lightning strikes, the problem of mismatch between trend of service requirement development and functions combination of OTN equipment.The background and principles of the above three issues were briefly sorted out and introduced.The forward and backward Raman amplifiers and remote optical pumping amplifiers were applied in the practical OTN system construction project.Theoretical calculations of the optical power distribution along the fiber were carried out and verified by field measured data, which quantitatively proved the gain of amplifiers mentioned above on the single-span transmission distance of OTN systems.The speed of the rotation of SOP caused by natural lightning strikes was theoretically estimated and measured in the practical OTN system.A test method for the SOP tracking ability of the OTN systems was proposed and carried out.An idea of applying the pakect optical transport network (POTN) to imporve the flexibility of OTN bandwidth administration was proposed.